Peran Komunitas Info Seputar Trenggalek dalam Pengentasan Kemiskinan di Kabupaten Trenggalek Sebagai Wujud dari Kegiatan Masyarakat Madani - Mifdal, Mifdal Zusron Alfaqi (Universitas Nusantara PGRI Kediri, 2022)
Trenggalek Regency has a big problem with a fairly high poverty rate. This research examines the role of the Info Seputar Trenggalek community in reducing poverty as a form of community independent action without waiting for action from the government in unraveling social problems called civil society. The method used is a qualitative approach with a case study design for 2 (two) years, starting from 2020 to 2021. The results showed that 1) the Info Seputar Trenggalek community was able to run various programs (Compensation for orphans and duafa, house surgery, educational assistance, opening tourist destinations, volunteering for the look down poverty movement (Gertak)) as a solution to poverty management; 2) the gap in the inhibition of activities arises because a) the limited funding is not proportional to the reported problem which is quite high; 3) The right design used is the problem-focus of community development that is tailored to the needs of the trenggalek community.